2016
DOI: 10.1016/j.neuron.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Tau Deposition in the Aging Human Brain

Abstract: SUMMARY Tau pathology is a hallmark of Alzheimer’s disease (AD) but also occurs in normal cognitive aging. Using the tau PET agent 18F-AV-1451, we examined retention patterns in cognitively normal older people in relation to young controls and AD patients. Age and β-amyloid (measured using PiB PET) were differentially associated with tau tracer retention in healthy aging. Older age was related to increased tracer retention in regions of the medial temporal lobe, which predicted worse episodic memory performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

105
1,001
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 986 publications
(1,156 citation statements)
references
References 59 publications
105
1,001
2
8
Order By: Relevance
“…It is therefore not entirely clear whether the results could be generalized to other tracers. Overall, results are similar to what has been reported for 18F-AV1451 (aka T807) [9]. Recently, the Tohoku group has released yet another tracer from the same series, THK5351, claiming improved kinetics but otherwise comparable properties [3].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…It is therefore not entirely clear whether the results could be generalized to other tracers. Overall, results are similar to what has been reported for 18F-AV1451 (aka T807) [9]. Recently, the Tohoku group has released yet another tracer from the same series, THK5351, claiming improved kinetics but otherwise comparable properties [3].…”
supporting
confidence: 86%
“…PART is characterised by mesial temporal tau deposits in the absence of beta-amyloid plaques and is usually regarded as a relatively benign age-related condition that is different from AD [6]. This issue has been addressed in a recent study using another tau tracer, 18F-AV145, which demonstrated that elderly normal controls do show increased hippocampal tau signal, but with less intensity and extent than what is typically seen in subjects with amyloidpositive scans [9].Chiotis et al also show positive regional correlations of tau with amyloid PET, as to be expected in AD as both pathological proteins accumulate. A predominantly negative This Editorial Commentary refers to the article http://dx…”
mentioning
confidence: 99%
“…[28][29][30] In this study, we used [ 18 F] THK5317 PET imaging in a longitudinal, multimodal design to investigate in vivo the propagation of tau pathology in a cohort of patients with AD and cases with CBS, in relation to markers of glucose metabolism and cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…1). Specifically, patients with AD show significant tau PET tracer uptake in the temporal, parietal, and frontal lobes, while the primary sensory/motor cortices are relatively spared [30,[39][40][41][42][43][44]. Tau in the inferior temporal lobe is associated with increased amyloid deposition on PET, as well as greater cognitive impairment and disease severity in AD [41,44].…”
Section: Tau Imaging Research Findingsmentioning
confidence: 99%
“…Notably, patients with MCI who are amyloid positive on PET showed much greater tau binding than those who were amyloid negative on PET, who rarely showed a Braak stage > 0 [44]. Finally, in CN adults only, amyloid positivity on PET is associated with increased tau tracer uptake in the medial and lateral temporal and parietal lobes [39,43]. A potential limiting factor for tau PET imaging is that Braak staging does not correlate perfectly with clinical symptomatology.…”
Section: Tau Imaging Research Findingsmentioning
confidence: 99%